Biomechanical Testing of a Calcium Phosphate-Phosphoserine–Based Mineral-Organic Adhesive for Non-invasive Fracture Repair of Mandibular Fractures in Dogs - Geddes, Alexander T.; Thatcher, Graham P.; Hetzel, Scott; McCabe, Ronald P.; Vandereby, Ray; Snyder, Christopher J. (Frontiers in Veterinary Science, 2020)
Mandibular fracture repair is complicated by limited availability of bone as well as the presence of the neurovascular bundle and an abundance of tooth roots. Fractures at the location of the mandibular first molar teeth are common and can be particularly challenging to apply stable fixation. Non-invasive fracture repair techniques utilize intraoral placement of fixation devices typically involving polymerized composites and/or interdental wiring. A novel calcium phosphate -phosphoserine based mineral-organic adhesive was tested ex-vivo to determined its effects on augmenting strength of different non-invasive fracture fixation techniques. This study tested both the use of mineral-organic adhesive for the purpose of stabilizing currently used non-invasive fracture repair constructs (intraoral composite splinting +/- interdental wiring) as well as evaluated adhesive alone or with subperiosteally placed plates on buccal cortical bone surface. Aside from controls, not receiving an osteotomy along the mesial root of mandibular first molar tooth, six treatment groups were tested to evaluate ultimate strength, stiffness, angular displacement, bending moment, and application time. All forms of fixation were found to be significantly weaker than control (p<0.001). Only the control (p<0.001) and mineral-organic adhesive and composite (p=0.002) groups were found to be significantly stronger than wire and composite. No difference was noted in stiffness between any groups with control or wire and composite. Application times varied from the mineral-organic adhesive group (mean = 206 seconds) to mineral-organic adhesive and composite (mean = 1281 seconds). Twenty-three fixation devices exhibited adhesive failure, 20 demonstrated cohesive failure and 5 failed by cohesive and adhesive failure. When evaluating the ultimate strength of the fixation device groups, mineral-organic adhesive and composite was shown to be the strongest construct. The use of resorbable bone adhesive and composite may provide a stronger fixation construct over interdental wire and composite for mandibular fracture repair in dogs.